Study the Effect of Hybrid Nanofillers Content on the X-ray Diffraction and Thermal Conductivity Properties of Epoxy-Based Nanocomposites - Alhussiny, Hajer; Albozahid, Muayad (Al-Nahrain Journal for Engineering Sciences, 2024)
High-performance polymer nanocomposites utilizing different-sized nanofillers had a lot of interest recently. Due to their distinct structural, and thermal characteristics. Multi-wall carbon nanotubes (MWCNT) and nanoclay (NC) have the most interest among the numerous types of reinforcing as filler elements for a polymer. The formation of hybrid from MWCNT and NC at various loadings (0.5%, 1%, and 2wt%) on the characteristics of epoxy polymer have been assessed in this work. The specimens have been created using solution blending procedures with the addition of solvent ethanol at a ratio of 1:1 for dispersed nanofillers, and then they have been re-mixed with epoxy. Tests like X-Ray diffraction (XRD), and thermal conductivity were used to identify properties of epoxy. According to the test results, the thermal conductivity rise as the filler content rises at 1wt%, then start to decrease after 1wt%. The sample with the hybrid filler loading of 1 wt% produced the best performance. Since hybrid epoxy exhibits the best result of the thermal conductivity 135% over MWNT and NC nanocomposites of 1 wt.% reached 0.3568 W/m.K in the increased thermal conductivity property. By examining the EP nanocomposites XRD pattern. The hybrid of epoxy nanocomposites exhibits all of the NC and MWCNT characteristic peaks. Since interactions between the filler and the epoxy cause a shift in the peak location of 1wt%. Due to the homogeneity of the nanofillers entire epoxy matrix, there may be changes in the intensity or location of the peaks at 1% for 2θ= 20.13°, which corresponds to an interlayer distance of d=0.461nm.